Paliperidone Long-Acting Plasma Level Monitoring and a New Method of Evaluation of Clinical Stability - Mauri, Massimo Carlo; Paletta, Silvia; Di Pace, Chiara; Reggiori, Alessandra; Rovera, Chiara; Fiorentini, Alessio; Altamura, Carlo Alfredo (Pharmacopsychiatry, 2017)
The second generation long-acting antipsychotics can be a pharmacologic strategy, both in the early phase of illness and in the case of low compliance. The aim of the study was to evaluate the clinical efficacy and tolerability of one monthly injection of paliperidone palmitate (PP1M), paliperidone plasma levels (PLs), and the clinical outcome. 21 outpatients, affected by Schizophrenia or Schizoaffective Disorder, were recruited. PP1M started with 150 mg on day 1 and 100 mg on day 8. Following patients were given a dosage ranging from 50 mg to 150 mg every 28 days. At baseline, and then monthly, patients were clinically evaluated. BPRS and PANSS total score showed a statistically significant decrease from T2 (after 2 months) to T12 (after 12 months). The PLs steady-state was approximatively reached after the fifth injection (T4). All the patients showed a clinical stabilization: BPRS and PANSS scores showed a significant improvement from T2. PLs data seems to suggest the initial possibility of an oral supplementation, although clinical evaluation demonstrated no relapse during the study.
Keywords: long acting injectable; plasma level; paliperidone palmitate; Schizophrenia